PENGARUH SISTEM ANTRIAN ONLINE TERHADAP KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS AIK MUAL - M. Yuza Royandi; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
The analysis of the relationship between the online registration system and patient satisfaction showed a significant correlation. The simple linear regression analysis, based on the significance value obtained in the table above, was 0.027 < 0.05, thus concluding that there is a significant correlation between patient satisfaction and the online registration system at the Aik Mual Community Health Center in Central Lombok.